(untitled) - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The objective of the research was to describe the receptive vocabulary in children of 8 and 9 years of an Educational Institution in Colombia. The research is descriptive, with a quantitative approach, non-experimental and cross-sectional design. A sample is composed of 86 children, according to inclusion and exclusion criteria. Results showed that the population obtained low, moderately low and very low scores. The data acquired lead us to conclude that when children live in culturally impoverished environments or with a family that is emotionally neglected, they will study with a poor vocabulary and telegraphic language. Therefore, in the short and medium term children will manifest problems related to basic skills for learning, specifically, with reading and writing issues that generally are closely linked to other difficulties of the language andvocabulary skills. As well, it is important to get on the specific components that give the identification, the concept and the categorization of the proposed stimulus, thisshould be studied in the sample and the relationship between the vocabulary analyzed and reading comprehension established.